~ Simplifying
-2(7x + -5) = -14x + 10
~ Reorder the terms:
-2(-5 + 7x) = -14x + 10
(-5 * -2 + 7x * -2) = -14x + 10
(10 + -14x) = -14x + 10
~ Reorder the terms:
10 + -14x = 10 + -14x
~ Add '-10' to each side of the equation.
10 + -10 + -14x = 10 + -10 + -14x
~ Combine like terms: 10 + -10 = 0
0 + -14x = 10 + -10 + -14x
-14x = 10 + -10 + -14x
~ Combine like terms: 10 + -10 = 0
-14x = 0 + -14x
-14x = -14x
~ Add '14x' to each side of the equation.
-14x + 14x = -14x + 14x
~ Combine like terms: -14x + 14x = 0
0 = -14x + 14x
~ Combine like terms: -14x + 14x = 0
0 = 0
~ Solving
0 = 0
~ This equation is an identity, all real numbers are solutions.